Effect of travel speed on seed spacing uniformity of corn seed meter - Quanwei, Liu; Xiantao, He; Li, Yang; Dongxing, Zhang; Tao, Cui; Zhe, Qu; Bingxin, Yan; Mantao, Wang; Tianliang, Zhang (International Journal of Agricultural and Biological Engineering, 2017)
Both seeding performance of seed metering unit and travel speed of seed planter have significant effects on seeding quality, thereby affecting crop growth and yields. In order to determine the effects of different travel speeds on seed spacing uniformity, four different types of seed meters were evaluated at five different travel speeds on seed meter test bench and in field. The tested seed meters included a finger pickup seed meter, a scoop-wheel seed meter, an air-pressure type seed meter and an air-blowing type seed meter. The seeding performance of the horizontal distribution of seeds within a row was described by using the coefficient of variation, the quality of feed index, the multiple index and the miss-seeding index. Experiments were performed in laboratory and field, respectively. Results indicated that different travel speeds have statistically significant effects on seed spacing uniformity. The four types of seed meters performed better on the seed meter test bench than in the field. Coefficient of variation increases and quality of feed index decreases as the travel speed of seed planter increases. The best seed spacing uniformity was obtained with the air-pressure type seed meter, followed with the air-blowing type seed meter, the finger pickup seed meter and the scoop-wheel seed meter. There were considerable differences between the performances of the scoop-wheel seed meter in the bench test and field test; the seeding qualities were much better in the bench test than in the field test. The scoop-wheel seed meter is more sensitive to vibration than the other types of seed meters. Keywords: corn seed meter, travel speed, seed spacing uniformity, precision corn planter, field test, test bench DOI: 10.25165/j.ijabe.20171004.2675 Citation: Liu Q W, He X T, Yang L, Zhang D X, Cui T, Qu Z, et al. Effect of travel speed on seed spacing uniformity of corn seed meter. Int J Agric & Biol Eng, 2017; 10(4): 98–106.